Sex and ecosystem services: the importance of gendered ethnobotanical knowledge in the Bale Mountains, Ethiopia - Luizza, Matt, speaker (Colorado State University. Libraries, 2013)
Integrating local ecological knowledge (LEK) of resource users with conventional scientific methods can promote effective collaboration among diverse stakeholders, facilitate access to decision-making power for marginalized communities, and provide a more holistic understanding of the landscape in question. Although this LEK integration is inherent to ethnobotanical studies, the importance of the knowledge-gender link is often overlooked. Understanding gender-based differences in local knowledge of plants is important for promoting collaborative conservation of plant-derived ecosystem services. Building on existing research of men's knowledge of plants in the Bale Mountains of Ethiopia and extensive vegetation data collected by the Natural Resource Ecology Laboratory, Matt conducted semi-structured interviews and focus groups to catalogue women's knowledge of plants in the Bale Mountains. This mixture of ecological field data and ethnobotanical data were examined in an effort to understand gender-based differences in plant-derived ecosystem services and the relative scarcity and abundance of service-providing plants across the landscape.
Presented at the Spring 2013 Center for Collaborative Conservation (https://collaborativeconservation.org/) Seminar and Discussion Series, "Collaborative Conservation in Practice: Innovations in Communities around the World", April 23, 2013, Colorado State University, Fort Collins, Colorado. This series focused on the work that the CCC's Collaborative Conservation Fellows have been doing across the Western U.S. and around the world.
Matt Luizza is a second year Ph.D. student in the Graduate Degree Program in Ecology, and a USDA National Needs Agricultural Biosecurity Fellow, working with advisor Michele Betsill (Political Science) and co‐advisor Paul Evangelista (Natural Resource Ecology Laboratory). His Ph.D. research explores the integration of local ecological knowledge (LEK) into modeling ecosystem service vulnerability to invasive species in the Yukon River Watershed of Alaska. Additionally, his research addresses the implications of this integrative spatial modeling methodology for adaptive governance of invasive species in the region.
Includes recorded speech and PowerPoint presentation.
Accessibility features: Unedited transcript.
Keywords: ecosystem services; adaptive governance; species distribution modeling